Sociocultural Awareness, Cultural Perspectives and Strategies in Language Assistants’ Academic Papers in Spain - Bianca Vitalaru (Tejuelo: Didáctica de la Lengua y la Literatura)
This paper includes an analysis of academic papers that focus on cultural aspects written by MA students in the ‘Teach & Learn in Spain’ program at Instituto Franklin-UAH. The percentage of academic papers focusing on cultural aspects written by these students who acted as Language Assistants (LAs) in bilingual schools in Spain is quite high. This suggests the importance of the cultural component in the teaching of English as a second language and their high level of sociocultural awareness. Thus, this paper has several objectives: a) to determine the existence of a specific sociocultural awareness in research papers; b) to identify the cultural aspects that were considered essential by the LAs in this program and show the strategies used to provide information; and c) to compare findings considering the theoretical background. The method will rely on a mixt approach considering quantitative and qualitative analyses and will be specific for each of the objectives.